1987
DOI: 10.1172/jci112978
|View full text |Cite
|
Sign up to set email alerts
|

Variation of erythroid and myeloid precursors in the marrow and peripheral blood of volunteer subjects infected with human parvovirus (B19).

Abstract: Infection of normal individuals with human parvovirus (B19) results in a mild disease (erythema infectiosum) but gives rise to aplastic crises in patients with chronic hemolytic anemias. The effects of this disease on hemopoiesis were investigated following intranasal inoculation of the virus into three volunteers. A typical disease ensued with a viremia peaking at 9 d. Marrow morphology 6 d after inoculation appeared normal but at 10 d there was a severe loss of erythroid precursors followed by a 1-2-g dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 22 publications
5
79
0
3
Order By: Relevance
“…However, the effect will be higher in tropical regions where there are underlying conditions or factors that will favour severe anaemia. The contribution of B19V to severe anaemia is also supported by the understanding that it causes a 2.0 g/dL decrease in haemoglobin level, even in adult volunteers with haemolytic disease who were previously healthy [27] . With this finding, the hypothesis that B19V may exacerbate severe anaemia in persons with underlying mild anaemia cannot be overemphasised.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the effect will be higher in tropical regions where there are underlying conditions or factors that will favour severe anaemia. The contribution of B19V to severe anaemia is also supported by the understanding that it causes a 2.0 g/dL decrease in haemoglobin level, even in adult volunteers with haemolytic disease who were previously healthy [27] . With this finding, the hypothesis that B19V may exacerbate severe anaemia in persons with underlying mild anaemia cannot be overemphasised.…”
Section: Discussionmentioning
confidence: 85%
“…B19V infection leads to a suppression of the bone marrow [27,28] . In patients with underlying haemolysis, acute B19V infection may lead to transient aplastic crisis, an abrupt and severe anaemia due to failure of red-cell production [29,30] .…”
Section: P E E R R E V I E W Abstractmentioning
confidence: 99%
“…Studies of healthy volunteers show that after a prodrome of constitutional symptoms, erythroid progenitor cells in the bone marrow are transiently depleted with a precipitous drop in reticulocyte counts followed by a mild anemia (rarely clinically apparent) as well as occasional leukopenia and thrombocytopenia [5]. Clearance of parvovirus infection is associated with the appearance of serum IgM antibodies, and by the third week after acute infection, specific IgG antibodies are formed.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the relationships between infectivity, dot-blot positivity and the development of a specific antibody response noted in this volunteer were consistent features of BI9 infection, 31 archival serum samples obtained at different times from eight other volunteers during previous studies (Anderson et al, 1985b;Potter et al, 1987) were tested in a similar manner. Between three and five samples from each individual were used and the results are shown in Fig.…”
mentioning
confidence: 97%
“…B19's ability to suppress erythroid colony formation in vitro has been used in a research setting to demonstrate infectivity in serum samples Young et al, 1984;Saarinen et al, 1986;Potter et al, 1987) but such clonogenic assays require at least a week to produce results. Using an adaptation of the culture system described by Yaegashi et al (1989) employing haematopoietic cells derived from first trimester foetal liver, we have previously shown that intracellular B19 nucleic acid can be detected in erythroid precursors by non-isotopic in situ hybridization within 8 h of inoculation (Morey & Fleming, 1992).…”
mentioning
confidence: 99%